DEIKSIS DALAM KOLOM OPINI PADA SURAT KABAR PONTIANAK POST EDISI MEI 2020 - Suci Ayu Lestari; Ahmad Rabi’ul Muzammil; Mellisa Jupitasari (Universitas Tanjungpura, 2022)
The purpose of this study was to describe the form and meaning of persona, place, and time deixis in the May 2020 edition of Pontianak Post newspaper opinion column and the implementation of deixis in Indonesian language learning. The form of this research was gualitative with descriptive method. The data in this research was the person deixis, place and time in May 2020 edition of Pontianak Post newspaper opinion column. The source of this research was the Pontianak Post newspaper in Mey 2020 edition. The data collection technigue in this research was using documentary The technigue testing the validity of data in this research was diligence of observation and reference coverage. The results of the study found 335 data forms of personal deixis, 11 data forms of place deixis and 24 data forms of time deixis. The forms of personal deixis found are singular and plural first person deixis, singular and plural second person, and singular and plural third person. Persona deixis means referential and constructional. The form of place deixis found is a reference to a place that is far from the speaker, a reference to a place that is not far from the speaker and a reference to a place that is close to the speaker. Place deixis means construction and referential. The form of time deixis is the time of past events, the time of present events and the time of future events. Time deixis means referential.